Nanostructured Lipid Carrier–Mediated Transdermal Delivery of Aceclofenac Hydrogel Present an Effective Therapeutic Approach for Inflammatory Diseases - Garg, Neeraj K.; Tandel, Nikunj; Bhadada, Sanjay Kumar; Tyagi, Rajeev K. (Frontiers in Pharmacology, 2021)
Aceclofenac (ACE), a COX-2 inhibitor, is the derivative of diclofenac group which has been in-use for symptomatic treatment of systemic inflammatory autoimmune disease, rheumatoid arthritis (RA).Partial solubility, high lipophilic nature, and stability questions its use to develop topical formulation. Hence, we developed and characterize nanostructured lipid carriers (NLCs) based aceclofenac hydrogel for an efficient transdermal delivery. NLCs microemulsion were prepared by different lipids using various methods and characterized with respect to the particle size, zeta potential, surface morphology and drug encapsulation efficiency. The optimized NLCs formulation was incorporated into Carbopol® 940gel, and this arrangement was characterized and compared with existing market formulations to assess in vitro drug release, rheology, texture profile, in-vivo skin retention & permeation, and stability. Further, prepared and characterized aceclofenac loaded NLC formulation was evaluated for skin integrity and fitted in the dermatokinetic model. Our results confirmed the spherical shape, smooth and nanometric size attested by Zeta sizer, scanning and transmission electron microcopy, and stability of ACE-NLCs formulation .NLC-based aceclofenac gel formulation showed good rheological and texture characteristics, better skin distribution in the epidermis and dermis. Moreover, ACE-NLCs permeated deeper in the skin layers and kept the skin integrity intact. Overall, NLCs based gel formulation of aceclofenac might be a promising nanoscale lipid carrier for topical application as compared to the conventional market formulation.